TANTANGAN BERAT REGENERASI PETANI BALI DALAM MEMPERTAHANKAN SUBAK SEBAGAI WARISAN BUDAYA DUNIA - I Made Dwipradnyana (AGRICA, 2017)
Heavy Challenge of Bali Farmers Regeneration in Supporting Subak as Worldwide Cultural World. The problem facing Indonesian agriculture is the regeneration of farmers. Regeneration is important because based on data from the Badan Pusat Statistik (BPS) the number of farming business households experienced a drastic decrease that originally in the 2003 agricultural census amounted to 492,394 households in 2013 decreased to 408,233 households or decreased by 84,161 household. This will be a serious problem in maintaining the subak system that became world heritage because without regeneration of farmers by themselves the subak system will die. The regeneration of farmers has become a serious concern, the regeneration problem of this farmer looks mediocre, does not look important, does not have drastic impact, but one day will bring harmful effects in the community, especially for the sustainability of Subak in Bali. The challenge faced by regenerating farmers is that the agricultural sector is less competitive with the tourism sector, the risk of high failure in agriculture, the younger generation considers other sectors more economically and government favoring factors that are considered faster spur economic growth. Suggestions that can be given is the role of government should be enhanced by integrating tourism with agriculture so that there is a mutually beneficial relationship, multiply training and technology development and provide agribusiness terminals to facilitate farmers to market their agricultural products there is certainty for farmers where selling and the existence of price certainty